Associations of Sociodemographic Characteristics with Food Choice Motives’ Importance Among Mexican Adults: A Cross-Sectional Analysis - Miguel Amaury Salas-García; María Fernanda Bernal-Orozco; Andrés Díaz-López; Alejandra Betancourt-Núñez; Pablo Alejandro Nava-Amante; Barbara Vizmanos (Foods)
Several studies have explored food choice motives (FCMs), but their association with sociodemographic characteristics remains under-researched. This study aimed to examine the cross-sectional associations between sociodemographic factors and FCMs in a sample of Mexican adults. Sociodemographic data and eight FCMs’ importance (health and natural content, mood, convenience, sensory appeal, price, food identity, image, and environmental concern) measured with a 75-item Updated Food Choice Questionnaire were studied in 786 participants (70% women, mean age: 24.7 years). The adjusted estimates from multivariable linear regressions are reported. Higher relative importance of convenience, price, and image management (all, p < 0.05) were associated with men. Older participants (≥41 years) showed greater concern for environmental and wildlife awareness (EWA) (p = 0.04). Higher education was associated with higher appreciation of health and natural content and EWA (both, p < 0.05), and less of sensory appeal and mood (both, p < 0.05). Individuals in a relationship placed less importance on sensory appeal compared to singles (p = 0.008). Middle–low socioeconomic status was linked to higher importance of food identity (p = 0.039), while food insecurity was associated with higher concern for price and food identity (both, p < 0.05). Our findings highlight the influence of sociodemographic factors on FCMs that might act as barriers or drivers for adopting healthy diets.